The Analysis of Relationship between International Shipping and World Economy - Mavlit AKHTYAMOV; Natalia ZAVYALOVA; Valery LIKHOLETOV; Ksenia AIKHEL (Communications of International Proceedings, 2020)
The development of the world economy is the basis and premise for the steady growth of international shipping demand. The world economy is the foundation of international shipping, because international shipping can be said to be a service industry, which serves for international trade, and international trade is an important standard to measure the world economy (Frankel, 1989). From a quantitative point of view, this paper studies the influence and interaction between international shipping and the world economy through grey correlation analysis, and the influence of the world economy on international shipping is much greater than that of international shipping on the world economy. The demand for trade promotes the demand for transportation, and shipping, as a cheap and high-volume mode of transportation, is also needed. As for the original demand of trade demand, international shipping demand is a kind of derivative demand. Therefore, the rise and fall of international trade directly determines the rise and fall of shipping industry. As one of the important industries in the development of national economy, shipping industry has guaranteed and promoted the development of international trade activities, and made global integration possible In order to promote the transformation of shipping industry, adapt to the market economy environment as soon as possible, allocate shipping resources through the market, and help the more economic and more effective operation of shipping industry, a set of economic theoretical system and a new way of thinking should be established to adapt to the characteristics of shipping industry.
Keywords: International Shipping; World Economy; Grey Relational Analysis; International Trade; Logistics; Supply Chain; Transportation.